Complications and Mortality Characterization in Acute Ischemic Cerebrovascular Disease - Ricardo Leyva Tornés; Lázaro Ibrahim Romero García; Esther Mayor Guerra; Yordanis Páez Candelaria; Karima Gondres Legró; Pedro Alexei Bacardí Zapata (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Background: ischemic cerebrovascular diseases constitute a neurological emergency. Its prevalence is progressively increasing worldwide, as well as associated morbidity, general and premature mortality. It stands as an important health problem that must be analyzed from an interdisciplinary approach at all levels of health care. Objective: to describe the most frequent complications incidence in the patients suffering from cerebrovascular disease population, as well as the burden of mortality associated with this neurological damage. Method: a descriptive study was carried out in patients with ischemic cerebrovascular disease who leaved from the Neurology Service of the Saturnino Lora Torres Provincial Clinical Surgical Teaching Hospital in the 2017-2019 triennium. The variables selected were: sex, type of complications, topography of the lesion by neuroimaging, state at discharge, and direct cause of death. 95 % confidence intervals were computed. The non-parametric Chi squared test of independence was applied and a significance level α = 0.05 was selected. Results: male patients predominated, for 61.4 % of the sample. 30.7 % of the patients became complicated, for the predominance of nosocomial pneumonia (16.0 %) and nosocomial urinary infection (8.0 %). Nine patients died (10.2 %), mainly due to infectious lung diseases (44.5 % of the total number of deaths). Conclusions: infectious lung diseases and urinary tract infection are the complications to be controlled in the population of patients affected by ischemic cerebrovascular disease, mainly as a consequence of large hemispheric cerebrovascular lesions. Mortality from this disease is considered minimal.